Effect of sex on the weight gain of calves (Bubalus bubalis) reared in silvopastoral systems during the dry season - Efraín Chacón Condori; Luis A. de la Cruz-Cruz (Revista Científica)
This study aimed to evaluate the effect of sex on the weight gain of calves raised in silvopastoral systems. Beween 2019 and 2020, 30 calves divided into two groups according to sex (females and males) were evaluated. At birth, the calves were identified and weighed within the first hours after birth. Afterward, a weight measurement was performed monthly in the morning time until 18 months of age. Likewise, daily weight gains (kg) and final weight (kg) were calculated. From birth to weaning, the calves were kept in restricted suckling systems (after milking, they were held with the mother and fed with one-quarter of the udder and the residual milk). After weaning, the animals were abruptly separated and placed in 15 38-hectare paddocks with silvopastoral systems and rotational grazing in pastures with native and introduced grasses and natural shade. The data was analyzed by comparing means using Tukey’s test with a significance level of p<0.05. No effects of sex were observed on birth weight (37.66±0.24 and 37.46±0.24; p=0.5673), weaning weight (161.93±37.46 and 163.60±33.75; p=0.8991) and final weight (380.93±12.03 and 381.66 ±12.03; p= 0.9659) between females and males, respectively. Weight gains from birth to 6 months of age, from 6 months to 12 months, and from 12 months to 18 months were not significant between females and males (0.69±0.05 and 0.69±0.04; p=0.9653, 0.64 ±0.03 and 0.62±0.02; p=0.06229, 0.55±0.03 and 0.59±0.03; p=0.06229). Average daily gains between females and males (0.60±0.02 kg/day and 0.63±0.05, respectively) were not significant because of sex (p =0.9653). It is concluded that females and males reared in restricted suckling systems and later, in silvopastoral systems, show good productive performance under dry season conditions. It is necessary to carry out more studies in which physiological, hormonal, and behavioural variables are related to improve the understanding of the productive performance of water buffalo in silvopastoral systems.